Insulin Resistance as a Link between Amyloid-Beta and Tau Pathologies in Alzheimer’s Disease - Mullins, Roger J.; Diehl, Thomas C.; Chia, Chee W.; Kapogiannis, Dimitrios (Frontiers in Aging Neuroscience, 2017)
Current hypotheses and theories regarding the pathogenesis of AD heavily implicate brain IR as a key factor. Despite the many well-validated metrics for systemic IR, the absence of biomarkers for brain-specific IR represents a translational gap that hindered its study in living humans. In our lab, we have been working to develop biomarkers that reflect the common mechanisms of brain IR and AD that may be used to follow their engagement by experimental treatments. We present two promising biomarkers for brain IR in AD: insulin cascade mediators probed in extracellular vesicles (EVs) enriched for neuronal origin, and two-dimensional Magnetic Resonance Spectroscopy measures of brain glucose. As further evidence for a fundamental link between brain IR and AD, we provide a novel analysis demonstrating the close spatial correlation between brain expression of genes implicated in IR (using Allen Human Brain Atlas data) and tau and beta-amyloid pathologies. We proceed to propose the bold hypotheses that baseline differences in the metabolic reliance to glycolysis, and the expression of glucose transporters and insulin signaling genes, determine the vulnerability of different brain regions to Tau and/or Aβ pathology and that insulin resistance is a critical link between these two pathologies that define AD. Lastly, we provide an overview of ongoing clinical trials that target IR as an angle to treat AD and suggest how biomarkers may be used to evaluate treatment efficacy and target engagement.